SOME NEW GENERALIZED AGGREGATION OPERATORS FOR TRIANGULAR INTUITIONISTIC FUZZY NUMBERS AND APPLICATION TO MULTI-ATTRIBUTE GROUP DECISION MAKING: SUGGESTED MODIFICATIONS - MISHRA*, AKANSHA (International Journal of Mathematical Archive, 2018)
Wan et al. (Computers & Industrial Engineering, 93 (2016) 286-301) proposed triangular intuitionistic fuzzy generalized ordered weighted averaging (TIFGOWA) operator and proved some of its basic properties. In this paper, it is pointed out that the statement and proof of boundedness property of TIFGOWA operator, proposed by Wan et al. is not valid. Also, a valid statement and proof for the same is proposed.